Profilaxis antibiótica en cirugía digestiva Investigación clínica con cefoxitina - Barboza B., Eduardo (1984)
A group of 99 patients were operated on because of elective gastric and biliary pathology, as well as non perforated acute appendicitis, in a prospective, doble blind and ramdomized study comparing the prophylactic value of the cefoxitine versus placebo.  The cefoxitine or placebo were given at the operating table just before the skin incision and ended in the next four hours. During the operation cultures were taken for aerobic and anaerobic bacteria from the peritoneal bed and the subcutaneos tisue.  There was a significative lowering of the incidence and severity of the post-operative woend infections in the cefoxitine group (p=0.007) and also a significative reduction of the hospitalization time (p=0.01). There were no secondary effects and no mortality during the present study.